Clinico-Epidemiological And Microbiological Evolution Of Pertussis - I. V. Babachenko (Журнал инфектологии, 2014)
The article deals with the data, which manifests the increasing part of vaccinated children and children older, then 7 years, among the hospital patients with whooping cough in Saint-Petersburg during 1990-2006 yy. The researchers have described the dynamics of dominating serotype changes among the hospital patients from 1.2.3. between 1990-2000 up to 1.0.3. between 2002-2006 and molecular-genetic characteristics of 13 strains of B. рertussis. Analysis of the clinical picture of the disease among 138 children, producing strains of B. рertussis of serotypes 1.2.3. and 1.2.0. (93 children) or strains of B. рertussis of serotypes 1.0.3. (45 children) showed that biological strains mutability of B. рertussis causes changes in severity and clinical course of рertussis infection, without effecting the clinical picture of the disease. Strains of B. рertussis of serotypes 1.0.3., IVb EFPP-group (during electrophoresis in pulsating gel), pertussis toxin A, pertactin 2 are associated with less severe illness forms (by 2,5 times), as well as specific complications (breath-holding and pertussis encephalopathy).